Trustworthy Verification of Academic Credentials through Blockchain Technology - Kabashi, Faton; Snopçe, Halil; Luma, Artan; Neziri, Vehbi (International Journal of Online and Biomedical Engineering (iJOE), 2024)
The increasing demand for a secure and transparent mechanism for verifying academic credentials has led to the exploration of blockchain technology (BT) as a viable solution. This paper presents a three-layered application for the reliable verification of academic credentials, leveraging the immutable and decentralized nature of BT. The system includes a data layer (DL), a blockchain layer (BL), and an application layer (AL). The DL records student records, faculty staff records, and credentials. The BL utilizes smart contracts to record and verify academic records, ensuring their authenticity and integrity. The AL provides a userfriendly interface for various stakeholders, such as students, educational institutions, and employers, to communicate with the system. This effort aims to determine how BT can be utilized to enhance the security, transparency, and efficiency of academic credential verification processes. Efficiency in academic credential verification processes ultimately contributes to a more reliable and effective educational ecosystem.